Kajian Simbolisme Sego Langgi dalam Tradisi Haul Sunan Sendang - Al Farisi, M. Alan (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
This research is motivated by the author's interest in Sego Langgi, which is the favorite iftar menu of Sunan Sendang during fasting. The author feels that the selection of Sego Langgi as the breaking fast menu must have reasons, meanings, and philosophy. To understand the Sufistic meaning contained in Sego Langgi, the author conducted research titled